Top 100 most-cited articles on pelvic organ prolapse: a visualization and bibliometric analysis - Yang, Lu; Tao, Qin; Wu, Huaye; Yin, Litong; Wu, Xuemei; Xiong, Ying; Gan, Xiaoqin; Lin, Yonghong; Yu, Xia (Frontiers in Surgery, 2025)
IntroductionBibliometric analysis is a scientometric method that allows the quantitative analysis of publications. This study used the Web of Science database to perform a bibliometric analysis of the 100 most-cited articles in the field of pelvic organ prolapse (POP) to identify the key research themes and emerging topics within this area.MethodsWe collected pertinent publications from the Web of Science Core Collection (WoSCC). The search was conducted using the following keywords: “pelvic organ prolapse”, “pelvic organ prolapse” or “pelvic organ prolapses”. The search included all publication dates up to June 27, 2024, without any article type restrictions, and the articles were sorted based on their citation count. The top 100 articles with the most citations were included in the subsequent analyses. Several tools, including the Bibliometrix program in R, CiteSpace software, the Online Analysis Platform of Literature Metrology (https://bibliometric.com), and an online interface by Bibliometrix, were used to analyze the data.ResultsThe top 100 most cited articles in the field of POP were cited 26,894 times in total. These articles were published between 1993 and 2019, and the majority of them were published during the 10-year period from 2001 to 2010. The United States and the University of California, San Francisco, produced the most publications on this topic. The American Journal of Obstetrics and Gynecology had the greatest influence on POP research. The most prolific author in this field was Barber MD (n = 7). Epidemiological research and treatment, particularly in the area of tissue engineering, were the main focus and current trends in POP research.ConclusionThis study revealed key research areas and current research hotspots for POP, with a particular focus on epidemiological studies and surgical interventions, especially in the field of tissue engineering. It is suggested that the future research in this field should pay more attention to epidemiological research and treatment, so as to better understand the risk factors of the disease and the characteristics of the affected population, and expect high-quality curative effect and prevention.